Comparison of 10-2 and 24-2C Test Grids for Identifying Central Visual Field Defects in Glaucoma and Suspect Patients - Phu, Jack; Kalloniatis, Michael (Ophthalmology (Rochester, Minn.), 2021)
To compare the ability of 24-2C and 10-2 test grids in measuring visual field global indices, identifying central visual field defects, and facilitating macular structure-function analysis with OCT scans in glaucoma and glaucoma suspect patients. Prospective, cross-sectional study. One eye from 131 glaucoma and 57 glaucoma suspect patients recruited from a referral-only, university-based glaucoma clinic. Each subject underwent perimetric testing using 24-2C SITA-Faster and 10-2 SITA-Fast in random order, and Cirrus OCT macular imaging (Ganglion Cell Analysis) for structure-function correlations. Visual field global indices (mean deviation, pattern standard deviation, binarized "cluster" pass/fail, and central mean sensitivity), number and proportion of visual field defects, and structure-function concordance with the Cirrus OCT deviation map following visual field location displacement for correspondence with underlying retinal ganglion cell position. Global indices (mean deviation, pattern standard deviation, and central mean sensitivity) were similar between both grids. The 10-2 detected more defects compared with the 24-2C (P < 0.0001 for all patients, P = 0.006 for glaucoma patients). This was preserved when analyzing the proportion of defects in the central visual field for all patients (P = 0.02) but was not significantly different for glaucoma patients (P = 0.051). The 10-2 identified more central "clusters" of 2+ contiguous points of deficit (P < 0.0001). Structure-function comparisons performed at locations where visual field and OCT test locations were colocalized revealed greater concordance of structural and functional deficits using the 10-2 (P < 0.0001). The 10-2 took a median of 201 seconds, and the 24-2C took a median of 154 seconds, corresponding to the different thresholding algorithms. The 24-2C and 10-2 test grids return similar global indices of visual field performance and proportionally similar amounts of central visual field loss. The additional points in the 10-2 grid return more "clusters" of defects and a greater rate of structure-function concordance compared with the 24-2C test grid. Thus, the 24-2C can identify the presence of a clustered central visual field defect using similar probability criteria, whereas the 10-2 may be more useful in comprehensively characterizing the defect and predicting central visual function.